Exploring what synchronized physiological arousal can reveal about the social regulatory process in a collaborative argumentation activity - Li, Xiaoran; Hu, Wanqing; Li, Yanyan; Mao, Ziqi (Frontiers in Psychology, 2023)
Combining physiological measures with observational data (e.g., video or self-reports) to further capture and understand the temporal and cyclical process of social regulation has become a trend in the field. Synchronized physiological arousal are particularly meaningful situations in collaboration. However, little attention has been put to synchronized physiological arousal episodes and its relationship with social regulatory process. Additionally, only a few researches utilized heart rate as physiological measures in current collaboration literature. More research is necessary to reveal the potential of heart rate to expand the diversity of physiological indicators in the field. Therefore, the current study aimed to explore what synchronized physiological arousal can further reveal about the social regulatory process. To achieve the goal, this study designed a collaborative argumentation activity for undergraduates (mean age 20.3) and developed an arousal-regulation analysis platform, which could automatically detect synchronized physiological arousal in heart rate and align them with coding challenges and social regulation based on the timeline. Fourteen four-member groups were recruited. After analyzing both videos and heart rate data, several findings were obtained. First, only one-third of episodes were synchronized physiological arousal episodes and the situations where four members were all at arousal states were rare during collaborative argumentation. Second, synchronized physiological arousal was more sensitive to socio-emotional aspects of collaboration as the shared physiological arousal more frequently co-occurred with socio-emotional challenges as well as socio-emotional regulation while it happened the least under motivational challenges. Third, synchronized physiological arousal has also been found to be associated with the challenges being regulated. Finally, pedagogical implications were suggested.